Experimental Analysis of the Effectiveness of a Cyber-physical Robotic System to Assist Speech and Language Pathologists in High School - Eldon Glen Caldwell-Marin; Miguel Cazorla; Jose Maria Cañas-Plaza (Springer, 2023)
This research focuses on whether the use of a cyber-physical robotic system (CPRS) to assist Speech and Language Pathologists (SLP) in a Special Education service is beneficial. The research method is based on a quasi-experiment with a 2k design and a two-way ANOVA, implemented with real high school students over 10 weeks. It was found that the use of this CPRT could improve, preliminarily and as an initial exploratory finding, therapeutic speech effectiveness up to 11.3 percentage points with a statistical confidence of 95%, when SLPs work with students with mild articulation disorder and a restricted time for therapy, but especially when the technology is used without time constraints. It is concluded that assistive CPRT could be a causal factor of improvement in specific treatments performed by SLPs, with the statistical evidence being sufficiently significant (95%) to maintain scientific and educational interest in this research line in the future.